Consumer knowledge, risk perception and food-handling behaviors – A national survey in China. (April 2021) - Wang, Mingliang; Huang, Lian; Liang, Xia; Bai, Li
Abstract: Introduction: Foodborne diseases have threatened human health and undermined food industries both domestically and globally, and improper food-handling behaviors have been considered as an important reason. Understanding the key drivers of consumer food-handling behaviors to develop effective mitigation strategies for foodborne diseases is urgently needed. Method: We conducted the first national survey in China to investigate the consumers' food-handling knowledge, risk perception (include two aspects: perceived severity and perceived susceptibility) and practices (leftover processing and raw meat thawing) across different subgroups of consumers. 3050 consumers were interviewed by stratified and random sampling and 1780 valid questionnaires were returned. Results: The results showed that Chinese consumers averagely had 54% correct rate of food-handling knowledge, only 14% of consumers can always implement normative leftover processing and 11% for raw meat thawing and consumers had lower perceived susceptibility compared to perceived severity. We found knowledge, perceived susceptibility and perceived severity had a significant positive relationship to normative food-handling behaviors and perceived severity had the lowest correlation with both normative leftover processing and raw meat thawing. There were significant differences in knowledge, risk perception and normative behaviors between gender, age, educational levels and income levels. In addition, there is no difference in knowledge, risk perception and behaviors for rural and urban residence. Practical applications: The practical implications and customized programs of food safety education for different subgroups of consumers have been provided to improve food-handling behaviors and mitigate foodborne diseases in China. Highlights: This is the first study of Chinese consumers' knowledge, risk perception and food-handling behaviors. This study determines the relationships between knowledge, risk perception, and food-handling behaviors. The rural-urban difference myth is discovered. Only a few Chinese consumers can always implement normative food-handling behaviors. The results provide an insight into consumers' food safety education.